Full vs Partial Market Coverage with Minimum Quality Standards - Luca Lambertini; Giulio Ecchia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
The consequences of the adoption of quality standards on the extent of market coverage is investigated by modelling a game between regulator and low-quality firm in a vertically differentiated duopoly. The game has a unique equilibrium in the most part of the parameter range. There exists a non-negligible range where the game has no equilibrium in pure strategies. This result questions the feasibility of MQS regulation when firms endogenously determine market coverage.
Keywords: 330